2013
DOI: 10.1111/acfi.12035
|View full text |Cite
|
Sign up to set email alerts
|

A possible explanation of the gender gap among accounting academics: evidence from the choice of research field

Abstract: Despite the significant increase in the number of women in accounting research over past decades, the percentage of female full professors in accounting is still low. One of the problems may relate to the research area(s) they choose to specialize in. Is the relatively slow promotion of women due to their decision to concentrate in 'nonmainstream' fields of research? In this study, we collect data on 1,042 male and female accounting academics. Using the research interests declared on each academic web page, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 41 publications
(42 reference statements)
1
5
0
Order By: Relevance
“…Cullen and Christopher () examine the career progression of women accountants in the state public service of Western Australia and New South Wales and find that work‐related barriers are significantly negatively related to career progression. Gago and Macias () ask whether the lack of female professors in accounting can be attributed to female academics specializing in non‐mainstream fields. They examine the research interests of over 1,000 male and female academics and find no significant gender difference in the choice of research field and conclude that the lack of promotion of women cannot be put down to their choice regarding non‐mainstream fields.…”
Section: Resultsmentioning
confidence: 99%
“…Cullen and Christopher () examine the career progression of women accountants in the state public service of Western Australia and New South Wales and find that work‐related barriers are significantly negatively related to career progression. Gago and Macias () ask whether the lack of female professors in accounting can be attributed to female academics specializing in non‐mainstream fields. They examine the research interests of over 1,000 male and female academics and find no significant gender difference in the choice of research field and conclude that the lack of promotion of women cannot be put down to their choice regarding non‐mainstream fields.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have identified gender inequality at universities (Baldarelli, Baldo, & Vignini, 2016;De Paola & Scoppa, 2015;Galizzi & Siboni, 2016). The lower promotion rate of women to full accounting professor at university is one reason that women are unwilling to choose academia (Gago & Mac ıas, 2014). Women's career progress in academia in Italy is also hindered, so women's contributions to gender discourse on accounting was found to be less than that of men (Baldarelli et al, 2016).…”
Section: Gender Inequality In Academiamentioning
confidence: 99%
“…Researches of Female business leaders and economic performance are seldom conducted with global observational figures and business environment consideration (Fang et al, 2020). Accounting investigators illustrate insignificant gender differentiations (Gago and Macias, 2015). But in general, the problem of social class solidification is universal.…”
Section: Current Situation Of the Social Mobility Of Female Talents In Chinamentioning
confidence: 99%